ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI KONSENTRASI PASAR AUDIT DI INDONESIA (STUDI EMPIRIS PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI 2013-2016) - Andi Maulidi; Afifudin Afifudin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2017)
AbstractThis study is aims to see the effect of audit risk, audit quality and leverage. The Population inthis research is real estate and property companies that listed on BEI 2013-2016. Based onthe results of research is using purposive sampling method with logistic regression methodobtained the number of 42 company samples with test results; The simultaneous test ofAudit Rotation, Audit Quality, Leverage Simultaneously have effect toward Audit MarketConcentration. Partially Audit Rotation has effect toward Audit Market Concentration. Theresult of audit quality test partially, Audit Quality has not effect toward Audit MarketConcentration. Leverage test results partially, Debt Leverage effect toward Audit MarketConcentration.Keywords: Audit Rotation, Audit Quality, Leverage, Market Audit Concentration